2020
DOI: 10.1155/2020/1702935
|View full text |Cite
|
Sign up to set email alerts
|

Helminthostachys zeylanica Water Extract Ameliorates Airway Hyperresponsiveness and Eosinophil Infiltration by Reducing Oxidative Stress and Th2 Cytokine Production in a Mouse Asthma Model

Abstract: Helminthostachys zeylanica is a traditional folk herb used to improve inflammation and fever in Taiwan. Previous studies showed that H. zeylanica extract could ameliorate lipopolysaccharide-induced acute lung injury in mice. The aim of this study was to investigate whether H. zeylanica water (HZW) and ethyl acetate (HZE) extracts suppressed eosinophil infiltration and airway hyperresponsiveness (AHR) in asthmatic mice, and decreased the inflammatory response and oxidative stress in tracheal epithelial cells. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…During the process of developing asthma, inflammatory immune cells (neutrophils, eosinophils, monocytes, and macrophages) and epithelial cells produce ROS. By generation of ROS, higher content than the natural antioxidant capacity of the lungs, oxidative stress and cell damage occur [ 48 ]. Excessive oxidative stress has been reported to exacerbate sputum production and inflammation in the airways and damage respiratory epithelial cells [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the process of developing asthma, inflammatory immune cells (neutrophils, eosinophils, monocytes, and macrophages) and epithelial cells produce ROS. By generation of ROS, higher content than the natural antioxidant capacity of the lungs, oxidative stress and cell damage occur [ 48 ]. Excessive oxidative stress has been reported to exacerbate sputum production and inflammation in the airways and damage respiratory epithelial cells [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…These cells also release more inflammatory and oxidative molecules that damage lung cells and tissue [ 10 ]. The activated Th2 cells release high level of cytokines, including IL-4, IL-5, and IL-13, leading to trigger AHR, induce mast cells, infiltrate eosinophils into the lungs, and subsequently increase mucus secretion [ 48 ]. Several studies reported that the expression of TNF- α , TGF-b, IL-1B, and α -SMA genes is significantly increased in OVA-induced asthma in animals, which is consistent with our findings [ 13 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The units of OVA-IgG2a and OVA-IgG1were defined using OD 450 values from standard curves of pooled serum from OVA-sensitized mice. The levels of chemokines and cytokines in cell culture media and BALF were detected using the specific ELISA kit (R&D Systems, Minneapolis, MN, USA) [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Rhizomes show hepatoprotective [ 236 , 237 ], anti-inflammatory [ [238] , [239] , [240] ], antihyperuricemia [ 241 ], cytotoxic [ 242 ], anticancer [ 243 ], antidiabetic [ 244 ] and antibacterial [ 245 ] activities.…”
Section: Distribution Ethnomedicine Pharmacognosy and Phytochemistry ...mentioning
confidence: 99%